1995
DOI: 10.1063/1.360074
|View full text |Cite
|
Sign up to set email alerts
|

A mild electrochemical sulfur passivation method for GaAs(100) surfaces

Abstract: We have developed a mild electrochemical sulfurization technique which can form a very thick sulfide layer on GaAs(100) surface. This sulfide layer is quite stable in air. The photoluminescence spectrum of such anodic sulfurized GaAs surface shows a large intensity enhancement as compared with that of as-etched GaAs samples. No visual intensity decay occurs under the laser beam illumination after the sample has been maintained in air for more than seven months. The structure and composition of the passivation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…According to prior studies, the electrochemical sulfidation promotes high oxidation states compounds like Ga2S5 and As2S5 on the surface [9,16]. These high oxidation state sulfides provide more stable surface passivation than the dipping type sulfidation method [9,16]. Surprisingly, in our study eFS samples showed low PLI increase (Figure 2) as compared to PLI observed on SF samples (Figure 2).…”
Section: Resultssupporting
confidence: 38%
See 1 more Smart Citation
“…According to prior studies, the electrochemical sulfidation promotes high oxidation states compounds like Ga2S5 and As2S5 on the surface [9,16]. These high oxidation state sulfides provide more stable surface passivation than the dipping type sulfidation method [9,16]. Surprisingly, in our study eFS samples showed low PLI increase (Figure 2) as compared to PLI observed on SF samples (Figure 2).…”
Section: Resultssupporting
confidence: 38%
“…Also, the peak of the photoluminescence data shifted by 6 nm as compared to the peak of photoluminesce data for the S sample. According to prior studies, the electrochemical sulfidation promotes high oxidation states compounds like Ga2S5 and As2S5 on the surface [9,16]. These high oxidation state sulfides provide more stable surface passivation than the dipping type sulfidation method [9,16].…”
Section: Resultsmentioning
confidence: 97%
“…Recently, Chen et al have reported that (NH 4 ) 2 S treatment at 50 • C for 20 min as the best treatment condition for reducing the dark current of InGaP/GaAs heterojunction phototransistors (HPTs) [19]. Electrochemical passivation of GaAs surfaces with sulfide solutions has also been reported [20]. However, a systematic study of the process parameters during sulfur passivation of InGaAs/InP photodetectors has not been reported so far to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…13) Sulfur passivation is widely used on III-V compounds, for example, InP and GaAs. 11,[14][15][16] However, the native oxides are rarely removed completely when using the (NH 4 ) 2 S solution. 17) Usually, conventional SiO 2 growth methods such as chemical vapor deposition (CVD) and plasma-enhanced chemical vapor deposition (PECVD) are used for MOS fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…18) InP was observed to have similar properties to GaAs for (NH 4 ) 2 S passivation. 15,16) In addition, these high-temperature methods have other disadvantages such as thermal stress, doping redistribution and material inter-diffusion. Liquid-phase-deposited SiO 2 (LPD-SiO 2 ) has many advantages such as low-temperature (room temperature is permissible) deposition, high uniformity, and selectivity, and low cost.…”
Section: Introductionmentioning
confidence: 99%